Transitional health care for patients with Hirschsprung disease and anorectal malformations - Witvliet, M. J. (Tech Coloproctol, 2017)
BACKGROUND: Hirschsprung disease (HD) and anorectal malformations (ARM) are congenital disorders with potentially lifelong consequences. Although follow-up is performed in most pediatric patients, transfer to adult health care is often problematic. This study assesses transitional care with the help of questionnaires in consultation with adult patients. METHODS: This study was conducted in an outpatient clinic of a pediatric surgical center in the Netherlands. All patients born and treated for ARM or HD before 1992 were invited to visit our clinic. Patients completed questionnaires concerning disease-specific functioning and quality of life at an initial visit to in response to which individual treatment plans were modified. Patients were reviewed 1 year later. RESULTS: Twenty-seven patients (17 ARM and 10 HD), mean age 27.9 years (range 17–64 years) of the 168 invited visited the transitional clinic (17%). Passive fecal incontinence was reported by 7/27, other defecatory problems, including urge incontinence and incomplete evacuation in 17/27 and anal or abdominal pain reported by 9/27. Quality of life was lower than a matched population. Only 13/27 returned for repeat assessment at 1 year; however, a further 8 reported that that their problems had resolved. In those attending follow-up, negative thoughts and feelings about their condition had decreased and one more patient was fully continent. There was no change in quality of life, bowel function or pain recorded. Twelve out of thirteen patients reported that they had found the transitional clinic satisfactory. CONCLUSIONS: The transitional outpatient clinic provides care adapted to the needs and wishes of adult HD and ARM patients. It is a novel addition to quality of care of patients with complex congenital disorders.